Оптимізація витрат підприємства на захист інформації - Левітін, П. Є. (ХНУРЭ, 2009)
State standard DSTU 3396.1-96 defines the order or work on organization of information security. In the report the the question of optimization of information security cost is discussed for achieving the maximum profit from enterprise.